substituted silicon phosphate compounds
Patent Information
- Application Number
- KR1020237031160
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-04-21
- Filing Date
- 2021-11-04
- Publication Date
- 2026-09-16
- Estimated Expiration
- 2041-11-04
Smart Images

Figure 112023117543134-PCT00016_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to new uses of substituted silicon group phosphate compounds, electrolytes, and lithium-ion batteries. Background Technology
[0002] Lithium-ion batteries possess advantages such as high operating voltage, high specific energy density, long cycle life, low self-discharge rate, no memory effect, and low environmental pollution, and are already widely applied in various consumer electronics and power battery markets. With the widespread application of lithium-ion batteries, consumer demands regarding usage environments are continuously rising, while the requirements for the driving range of electronic equipment are also increasing; this is demanding that lithium-ion batteries possess higher energy densities.
[0003] In recent years, lithium-ion secondary batteries with higher energy densities have been sought, and one method is to use cathode and anode materials with high gram capacity. Currently, ternary high-nickel cathode materials and silicon-based anode materials are high-energy-density materials for lithium-ion batteries with very high potential. However, since high-nickel content materials are prone to water absorption, the Ni-O bond structure on the surface decomposes when environmental humidity is high, precipitating lithium to form basic substances such as lithium hydroxide and lithium carbonate. Consequently, electrolyte stability is degraded, and gas expansion of the battery at high temperatures becomes severe. Furthermore, silicon-based anode materials also have relatively significant disadvantages. One is that when silicon particles detach lithium, volume expansion and contraction occur, causing the particles to pulverize and detach, leading to structural collapse and a decrease in battery capacity; another is that due to the volume effect of silicon-based anode materials, the SEI film is continuously destroyed and repaired, while the electrolyte is continuously consumed and the internal resistance of the battery gradually increases, eventually causing the battery's electric charge to drop rapidly.
[0004] At the current stage, using additives in the electrolyte is the most efficient weapon for solving the above problems. Many researchers improve various battery performances by improving the quality of the SEI film through the addition of various film-forming additives (vinylene carbonate, fluoroethylene carbonate, vinyl ethylene carbonate, etc.) to the electrolyte. However, after the addition of fluoroethylene carbonate, the battery is prone to generating gas during high-temperature storage, causing it to swell and increasing impedance, which severely affects the battery's high-temperature performance. Therefore, there is an urgent need to develop lithium-ion battery electrolytes that can suppress gas expansion and reduce the impedance of the high-energy density system. The problem to be solved
[0005] In light of this, there is a need to provide new uses for substituted silicon-based phosphate compounds, as well as electrolytes and lithium-ion batteries. As an electrolyte additive, the substituted silicon-based phosphate compound can suppress gas expansion in the battery and reduce the impedance of the high energy density system. means of solving the problem
[0006] In the application of a substituted silicon group phosphate compound having the structure shown in formula (I) as an electrolyte additive,
[0007]
[0008] (I)
[0009] Here, R1, R2, R3, R4, R5, R6, R7, R8, and R9 are each independently C 1-8 Alkyl, C 2-8 Alkenes or C 2-8 Selected from alkynes;
[0010] Also, at least one of R1, R2, and R3 is C 1-8 They are alkyl, and one of them is C 2-8 Alkenes or C 2-8 It is an alkyne;
[0011] At least one of R4, R5, and R6 is C 1-8 They are alkyl, and one of them is C 2-8 Alkenes or C 2-8 It is an alkyne;
[0012] At least one of R7, R8, and R9 is C 1-8 They are alkyl, and one of them is C 2-8 Alkenes or C 2-8 It is Alkin.
[0013] In an electrolyte containing an additive, the additive comprises a substituted silicon group phosphate compound having the structure shown in formula (I), and
[0014]
[0015] (I)
[0016] Here, R1, R2, R3, R4, R5, R6, R7, R8, and R9 are each independently C 1-6 Alkyl, C 2-6 Alkenes or C 2-6 Selected from alkynes;
[0017] Also, at least one of R1, R2, and R3 is C 1-6 They are alkyl, and one of them is C 2-8 Alkenes or C 2-8 It is an alkyne;
[0018] At least one of R4, R5, and R6 is C 1-6 They are alkyl, and one of them is C 2-8 Alkenes or C 2-8 It is an alkyne;
[0019] At least one of R7, R8, and R9 is C 1-6 They are alkyl, and one of them is C 2-8 Alkenes or C 2-8 It is Alkin.
[0020] A lithium-ion battery comprises a positive electrode, a negative electrode, and the electrolyte described above. Effects of the invention
[0021] The present invention has the following beneficial effects.
[0022] Compared to conventional technology, the present invention uses a substituted silicon phosphate compound as an electrolyte additive. Since this type of material contains unsaturated groups, it polymerizes on the surfaces of the anode and cathode to form a stable interfacial film, thereby improving the cycle performance of the battery. Furthermore, by suppressing the oxidation reaction on the anode surface of the electrolyte, the leaching of metal ions can be effectively suppressed. By suppressing the oxidative decomposition of the electrolyte in a high-temperature environment and gas generation during the cycling process, the high-temperature storage performance and high-temperature cycle performance of the lithium-ion battery can be improved, thereby ensuring excellent performance of the lithium-ion battery. Additionally, it has been discovered that the content of unsaturated groups must be maintained within a certain range, and that too many unsaturated groups make the interfacial film too thick, increasing the internal resistance of the battery and hindering the performance of the battery. Brief explanation of the drawing
[0023] Figure 1 is a diagram showing the performance test of the battery of Example 1. Specific details for implementing the invention
[0024] Hereinafter, in order to facilitate understanding of the present invention, the invention is described more comprehensively and preferred embodiments of the invention are provided. However, the present invention may be embodied in various different forms and is not limited to the embodiments described herein. Conversely, the purpose of providing these embodiments is to provide a more thorough and comprehensive understanding of the disclosure of the present invention.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as generally understood by a person skilled in the art of the present invention. The terms used in the specification of the present invention are for the purpose of describing specific embodiments only and are not intended to limit the present invention. The term "and / or" used in this specification includes any combination and all combinations of one or more related listed items.
[0026] terminology
[0027] Unless otherwise specified or contradictory, terms or phrases used in this specification have the following meanings.
[0028] The term "alkyl" means a saturated hydrocarbon comprising a primary (positive) carbon atom, or a secondary carbon atom, or a tertiary carbon atom, or a combination thereof. Phrases containing said term, for example, "C 1-8"alkyl" means an alkyl group comprising 1 to 8 carbon atoms, and each time it appears, it may be independently C1-alkyl, C2-alkyl, C3-alkyl, C4-alkyl, C5-alkyl, C6-alkyl, C7-alkyl, or C8-alkyl. Suitable examples are methyl (Me, -CH3), ethyl (Et, -CH2CH3), 1-propyl (n-Pr, n-propyl, -CH2CH2CH3), 2-propyl (i-Pr, i-propyl, -CH(CH3)2), 1-butyl (n-Bu, n-butyl, -CH2CH2CH2CH3), 2-methyl-1-propyl (i-Bu, i-butyl, -CH2CH(CH3)2), 2-butyl (s-Bu, s-butyl, -CH(CH3)CH2CH3), 2-methyl-2-propyl (t-Bu, t-butyl, -C(CH3)3), 1-pentyl (n-amyl, -CH2CH2CH2CH2CH3), 2-amyl(-CH(CH3)CH2CH2CH3), 3-pentyl(-CH(CH2CH3)2), 2-methyl-2-butyl(-C(CH3)2CH2CH3), 3-methyl-2-butyl(-CH(CH3)CH(CH3)2), 3-methyl-1-butyl(-CH2CH2CH(CH3)2), 2-methyl-1-butyl(-CH2CH(CH3)CH2CH3), 1-hexyl(-CH2CH2CH2CH2CH2CH3), 2-hexyl(-CH(CH3)CH2CH2CH2CH3), 3-hexyl(-CH(CH2CH3)(CH2CH2CH3)), 2-methyl-2-pentyl(-C(CH3)2CH2CH2CH3), Includes, but is not limited to, 3-methyl-2-pentyl (-CH(CH3)CH(CH3)CH2CH3), 4-methyl-2-pentyl (-CH(CH3)CH2CH(CH3)2), 3-methyl-3-pentyl (-C(CH3)(CH2CH3)2), 2-methyl-3-pentyl (-CH(CH2CH3)CH(CH3)2), 2,3-dimethyl-2-butyl (-C(CH3)2CH(CH3)2), 3,3-dimethyl-2-butyl (-CH(CH3)C(CH3)3 and octyl (-(CH2)7CH3).
[0029] "Alkenyl" has at least one unsaturated site, i.e., carbon-carbon sp² 2It means a hydrocarbon containing a normal carbon atom, a secondary carbon atom, a tertiary carbon atom, or a cyclic carbon atom having a double bond. Phrases containing the term, for example, "C 2-8 "Alkenyl" means an alkenyl containing 2 to 8 carbon atoms, and each time it appears, it may be a C2 alkenyl, C3 alkenyl, C4 alkenyl, C5 alkenyl, C6 alkenyl, C7 alkenyl, or C8 alkenyl independently of each other. Suitable examples include, but are not limited to, vinyl (-CH=CH2), ylyl (-CH2CH=CH2), cyclopentenyl (-C5H7), and 5-hexenyl (-CH2CH2CH2CH2CH=CH2).
[0030] "Alkynyl" means a hydrocarbon comprising a normal carbon atom, a secondary carbon atom, a tertiary carbon atom, or a cyclic carbon atom having at least one unsaturated site, namely a carbon-carbon sp³ triple bond. Phrases containing said term, for example, "C 2-8 "Alkynyl" means an alkynyl containing 2 to 8 carbon atoms, and each time it appears, it may be a C2 alkynyl, C3 alkynyl, C4 alkynyl, C5 alkynyl, C6 alkynyl, C7 alkynyl, or C8 alkynyl independently of each other. Suitable examples include, but are not limited to, ethinyl (-C≡CH) and propargyl (-CH2C≡CH).
[0031] Detailed interpretation
[0032] One embodiment of the present invention provides an application of a substituted silicon group phosphate compound having the structure shown in formula (I) as an electrolyte additive, wherein
[0033]
[0034] (I)
[0035] Here, R1, R2, R3, R4, R5, R6, R7, R8, and R9 are each independently C 1-8 Alkyl, C 2-8 Alkenes or C 2-8 Selected from alkynes;
[0036] Also, at least one of R1, R2, and R3 is C 1-8 They are alkyl, and one of them is C 2-8 Alkenes or C 2-8 It is an alkyne;
[0037] At least one of R4, R5, and R6 is C 1-8 They are alkyl, and one of them is C 2-8 Alkenes or C 2-8 It is an alkyne;
[0038] At least one of R7, R8, and R9 is C 1-8 They are alkyl, and one of them is C 2-8 Alkenes or C 2-8 It is Alkin.
[0039] In some embodiments, R1, R2, R3, R4, R5, R6, R7, R8, and R9 are each independently C 1-6 Alkyl, C 2-6 Alkenes or C 2-6 It is selected from Alkyne.
[0040] In some embodiments, R1, R2, R3, R4, R5, R6, R7, R8, and R9 are each independently C 1-4 Alkyl, C 2-4 Alkenes or C 2-4 It is selected from Alkyne.
[0041] In some embodiments, R1, R3, R4, R6, R7 and R9 are each independently selected from vinyl, ethinyl, allyl, or propargyl; and R2, R5, and R8 are each independently selected from methyl, ethyl, 1-propyl, 2-propyl, 1-butyl, 2-methyl-1-propyl, or 2-butyl.
[0042] In some embodiments, R1, R3, R4, R6, R7 and R9 are each independently selected from methyl, ethyl, 1-propyl, 2-propyl, 1-butyl, 2-methyl-1-propyl, or 2-butyl; and R2, R5 and R8 are each independently selected from vinyl, ethinyl, allyl, or propargyl.
[0043] In some embodiments, at least two of -SiR1R2R3, -SiR4R5R6 and -SiR7R8R9 are identical to each other.
[0044] In some embodiments, -SiR1R2R3, -SiR4R5R6 and -SiR7R8R9 are identical to each other.
[0045] In some embodiments, it is selected from any of the following compounds.
[0046]
[0047]
[0048] One embodiment of the present invention relates to an electrolyte containing an additive, wherein the additive comprises a substituted silicon group phosphate compound having the structure shown in formula (I).
[0049]
[0050] (I)
[0051] Here, the definitions of each group have been explained above, so they will not be explained further here.
[0052] In some embodiments, the additive further comprises a second additive, the second additive being one or more of vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, vinyl sulfite, vinyl sulfate, and 1,3-propanesulfonic acid lactone.
[0053] In some embodiments, the mass percentage content of the additive in the electrolyte is 0.05% to 20.0%; furthermore, the mass percentage content of the additive is 0.1% to 15%; furthermore, the mass percentage content of the additive is 1% to 10%.
[0054] In some embodiments, the compound of the structure shown in formula (I) is a first additive, and the mass percentage content of the first additive in the electrolyte is 0.1% to 15%; furthermore, the mass percentage content of the first additive is 0.1% to 10%; furthermore, the mass percentage content of the first additive is 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%.
[0055] In some embodiments, the mass percentage content of the second additive in the electrolyte is 0.1% to 5%.
[0056] In some embodiments, the above-described electrolyte further comprises a lithium salt and a solvent, wherein the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium dioxalate borate, lithium difluorooxalate borate, lithium bisfluorosulfonyl imide and lithium bistrifluoromethanesulfonyl imide.
[0057] In some embodiments, the concentration of the lithium salt in the electrolyte is 0.5M to 1.5M; furthermore, the concentration of the lithium salt is 0.5M, 0.75M, 1M, 1.25M, and 1.5M.
[0058] In some embodiments, the solvent is selected from one or more of a chain-type carbonate-based solvent, a cyclic carbonate-based solvent, and a carboxylate-based solvent.
[0059] In some embodiments, the cyclic carbonate solvent is selected from one or more of vinyl carbonate (EC) and propylene carbonate (PC); in some embodiments, the chain carbonate solvent is selected from one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC), and methyl ethyl carbonate (EMC); and in some embodiments, the carboxylate solvent is selected from one or more of propyl acetate (PA), ethyl acetate (EA), and propyl propionate (PP).
[0060] In some embodiments, the solvent is a combination of vinyl carbonate (EC), diethyl carbonate (DEC) and methyl ethyl carbonate (EMC); furthermore, the mass ratio of vinyl carbonate (EC), diethyl carbonate (DEC) and methyl ethyl carbonate (EMC) is 1:(1-2):(1-2).
[0061] One embodiment of the present invention further provides a lithium-ion battery comprising a positive electrode, a negative electrode, and the electrolyte described above. As the electrolyte has been described above, it is not described further here.
[0062] In some embodiments, the anode material forming the anode comprises a lithium transition metal oxide, wherein the lithium transition metal oxide is LiCoO2, LiMn2O4, LiMnO2, Li2MnO4, LiFePO4, Li 1+a Mn 1-x M x O2, LiCo 1-x M x O2, LiFe 1-x M x PO4, Li2Mn 1-x O4, where M is selected from one or more of Ni, Co, Mn, Al, Cr, Mg, Zr, Mo, V, Ti, B, F, 0≤a<0.2, 0≤x<1.
[0063] In some embodiments, the cathode material forming the cathode is natural graphite, synthetic graphite, intermediate phase microcarbon spheres (abbreviated as MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structure lithiated TiO2-Li4Ti5O 12 It includes one or more of the Li-Al alloys.
[0064] The present invention will be explained below with reference to specific embodiments.
[0065]
[0066] Example 1
[0067] (1) Preparation of electrolyte: Vinyl carbonate (EC), diethyl carbonate (DEC) and methyl ethyl carbonate (EMC) were mixed in a mass ratio of EC:DEC:EMC = 20:25:32, then 1 mol of lithium hexafluorophosphate (LiPF6) was added, along with compound 1 additive which accounted for 1% of the total mass of the electrolyte, 1,3-propane sulfone (PS) which accounted for 2% of the total mass of the electrolyte, and fluoroethylene carbonate (FEC) which accounted for 5 wt% of the total mass of the electrolyte, and then uniformly stirred to obtain the electrolyte of a lithium-ion battery.
[0068] (2) Manufacture of anode sheet: nickel-cobalt-manganese-lithium ternary material LiNi 0.8 Co 0.1 Mn 0.1 A lithium-ion battery cathode slurry of constant viscosity was prepared by uniformly mixing O2, conductive agent SuperP, adhesive PVDF, and carbon nanotubes (CNT) in a mass ratio of 97.3:1:1.2:0.5, with a viscosity of 400 g / m² 2 A lithium-ion battery positive sheet that meets the requirements was manufactured by applying a coating amount onto an aluminum foil for a current collector, drying and rolling to obtain a positive sheet.
[0069] (3) Preparation of cathode sheet: Artificial graphite and silicon are mixed in a mass ratio of 90:10, and then a slurry is prepared with conductive agent SuperP, conductive agent CNT, thickener CMC, and adhesive SBR (butadiene styrene rubber latex) in a mass ratio of 95.64:1:0.06:1.3:2 and uniformly mixed, and the mixed slurry is 149 g / m² 2 A lithium-ion battery negative sheet that meets the requirements was manufactured by applying a coating amount to both sides of a copper foil, drying and rolling to obtain a negative sheet.
[0070] (4) Manufacture of a lithium-ion battery: A lithium-ion battery with a thickness of 4.7 mm, a width of 55 mm, and a length of 60 mm was manufactured by laminating the positive electrode sheet, negative electrode sheet, and diaphragm manufactured according to the above-described process, and the battery was manufactured by vacuum baking at 85°C for 48 hours and injecting the above-described electrolyte.
[0071] Example 2
[0072] (1) Preparation of electrolyte: Vinyl carbonate (EC), diethyl carbonate (DEC) and methyl ethyl carbonate (EMC) were mixed in a mass ratio of EC:DEC:EMC = 20:25:32, then 1 mol of lithium hexafluorophosphate (LiPF6) was added, along with compound 2 additive which accounted for 1% of the total mass of the electrolyte, 1,3-propane sulfone (PS) which accounted for 2% of the total mass of the electrolyte, and fluoroethylene carbonate (FEC) which accounted for 5 wt% of the total mass of the electrolyte, and then uniformly stirred to obtain the electrolyte of a lithium-ion battery.
[0073] (2) Manufacture of anode sheet: nickel-cobalt-manganese-lithium ternary material LiNi 0.8 Co 0.1 Mn 0.1 A lithium-ion battery cathode slurry of constant viscosity was prepared by uniformly mixing O2, conductive agent SuperP, adhesive PVDF, and carbon nanotubes (CNT) in a mass ratio of 97.3:1:1.2:0.5, with a viscosity of 400 g / m² 2 A lithium-ion battery positive sheet that meets the requirements was manufactured by applying a coating amount onto an aluminum foil for a current collector, drying and rolling to obtain a positive sheet.
[0074] (3) Preparation of cathode sheet: Artificial graphite and silicon are mixed in a mass ratio of 90:10, and then a slurry is prepared with conductive agent SuperP, conductive agent CNT, thickener CMC, and adhesive SBR (butadiene rubber latex) in a mass ratio of 95.64:1:0.06:1.3:2 and uniformly mixed, and the mixed slurry is 149 g / m² 2 A lithium-ion battery negative sheet that meets the requirements was manufactured by applying a coating amount to both sides of a copper foil, drying and rolling to obtain a negative sheet.
[0075] (4) Manufacture of a lithium-ion battery: A lithium-ion battery with a thickness of 4.7 mm, a width of 55 mm, and a length of 60 mm was manufactured by laminating the positive electrode sheet, negative electrode sheet, and diaphragm manufactured according to the above-described process, and the battery was manufactured by vacuum baking at 85°C for 48 hours and injecting the above-described electrolyte.
[0076] Example 3
[0077] (1) Preparation of electrolyte: Vinyl carbonate (EC), diethyl carbonate (DEC) and methyl ethyl carbonate (EMC) were mixed in a mass ratio of EC:DEC:EMC = 20:25:32, then 1 mol of lithium hexafluorophosphate (LiPF6) was added, along with compound 3 additive which accounted for 1% of the total mass of the electrolyte, 1,3-propane sulfone (PS) which accounted for 2% of the total mass of the electrolyte, and fluoroethylene carbonate (FEC) which accounted for 5 wt% of the total mass of the electrolyte, and then uniformly stirred to obtain the electrolyte of a lithium-ion battery.
[0078] (2) Manufacture of anode sheet: nickel-cobalt-manganese-lithium ternary material LiNi 0.8 Co 0.1 Mn 0.1A lithium-ion battery cathode slurry of constant viscosity was prepared by uniformly mixing O2, conductive agent SuperP, adhesive PVDF, and carbon nanotubes (CNT) in a mass ratio of 97.3:1:1.2:0.5, with a viscosity of 400 g / m² 2 A lithium-ion battery positive sheet that meets the requirements was manufactured by applying a coating amount onto an aluminum foil for a current collector, drying and rolling to obtain a positive sheet.
[0079] (3) Preparation of cathode sheet: Artificial graphite and silicon are mixed in a mass ratio of 90:10, and then a slurry is prepared with conductive agent SuperP, conductive agent CNT, thickener CMC, and adhesive SBR (butadiene styrene rubber latex) in a mass ratio of 95.64:1:0.06:1.3:2 and uniformly mixed, and the mixed slurry is 149 g / m² 2 A lithium-ion battery negative sheet that meets the requirements was manufactured by applying a coating amount to both sides of a copper foil, drying and rolling to obtain a negative sheet.
[0080] (4) Manufacture of a lithium-ion battery: A lithium-ion battery with a thickness of 4.7 mm, a width of 55 mm, and a length of 60 mm was manufactured by laminating the positive electrode sheet, negative electrode sheet, and diaphragm manufactured according to the above-described process, and the battery was manufactured by vacuum baking at 85°C for 48 hours and injecting the above-described electrolyte.
[0081] Example 4
[0082] (1) Preparation of electrolyte: Vinyl carbonate (EC), diethyl carbonate (DEC) and methyl ethyl carbonate (EMC) were mixed in a mass ratio of EC:DEC:EMC = 20:25:32, then 1 mol of lithium hexafluorophosphate (LiPF6) was added, along with compound 1 additive which accounted for 1% of the total mass of the electrolyte, 1,3-propane sulfone (PS) which accounted for 2% of the total mass of the electrolyte, and fluoroethylene carbonate (FEC) which accounted for 5 wt% of the total mass of the electrolyte, and then uniformly stirred to obtain the electrolyte of a lithium-ion battery.
[0083] (2) Preparation of anode sheet: A lithium-ion battery anode slurry of constant viscosity was prepared by uniformly mixing lithium cobaltate material LiCoO2, conductive agent SuperP, adhesive PVDF, and carbon nanotubes (CNT) in a mass ratio of 96.8:2:1.2:0.05, and 330 g / m² 2 A lithium-ion battery positive sheet that meets the requirements was manufactured by applying a coating amount onto an aluminum foil for a current collector, drying and rolling to obtain a positive sheet.
[0084] (3) Preparation of cathode sheet: Artificial graphite and silicon are mixed in a mass ratio of 90:10, and then a slurry is prepared with conductive agent SuperP, thickener CMC, and adhesive SBR (butadiene styrene rubber latex) in a mass ratio of 95:1.5:1.5:2:2 and uniformly mixed, and the mixed slurry is 157 g / m² 2 After applying the coating amount to both sides of the copper foil, drying and rolling were performed to obtain a negative electrode sheet, thereby manufacturing a lithium-ion battery negative electrode sheet that meets the requirements.
[0085] (4) Manufacture of a lithium-ion battery: A lithium-ion battery with a thickness of 4.7 mm, a width of 55 mm, and a length of 60 mm was manufactured by laminating the positive electrode sheet, negative electrode sheet, and diaphragm manufactured according to the above-described process, and the battery was manufactured by vacuum baking at 85°C for 48 hours and injecting the above-described electrolyte.
[0086] Example 5
[0087] (1) Preparation of electrolyte: Vinyl carbonate (EC), diethyl carbonate (DEC) and methyl ethyl carbonate (EMC) were mixed in a mass ratio of EC:DEC:EMC = 20:25:32, then 1 mol of lithium hexafluorophosphate (LiPF6) was added, along with compound 2 additive which accounted for 1% of the total mass of the electrolyte, 1,3-propane sulfone (PS) which accounted for 2% of the total mass of the electrolyte, and fluoroethylene carbonate (FEC) which accounted for 5 wt% of the total mass of the electrolyte. After uniform stirring, the electrolyte of the lithium-ion battery was obtained.
[0088] (2) Preparation of anode sheet: A lithium-ion battery anode slurry of constant viscosity was prepared by uniformly mixing lithium cobaltate material LiCoO2, conductive agent SuperP, adhesive PVDF, and carbon nanotubes (CNT) in a mass ratio of 96.8:2:1.2:0.05, and 330 g / m² 2 of A lithium-ion battery positive electrode sheet meeting the requirements was manufactured by applying a coating amount onto an aluminum foil for a current collector, drying, and rolling to obtain a positive electrode sheet.
[0089] (3) Preparation of cathode sheet: Artificial graphite and silicon are mixed in a mass ratio of 90:10, and then a slurry is prepared with conductive agent SuperP, thickener CMC, and adhesive SBR (butadiene styrene rubber latex) in a mass ratio of 95:1.5:1.5:2:2 and uniformly mixed, and the mixed slurry is 157 g / m² 2After applying the coating amount to both sides of the copper foil, drying and rolling were performed to obtain a negative electrode sheet, thereby manufacturing a lithium-ion battery negative electrode sheet that meets the requirements.
[0090] (4) Manufacture of a lithium-ion battery: A lithium-ion battery with a thickness of 4.7 mm, a width of 55 mm, and a length of 60 mm was manufactured by laminating the positive electrode sheet, negative electrode sheet, and diaphragm manufactured according to the above-described process, and the battery was manufactured by vacuum baking at 85°C for 48 hours and injecting the above-described electrolyte.
[0091] Example 6
[0092] (1) Preparation of electrolyte: Vinyl carbonate (EC), diethyl carbonate (DEC) and methyl ethyl carbonate (EMC) were mixed in a mass ratio of EC:DEC:EMC = 20:25:32, then 1 mol of lithium hexafluorophosphate (LiPF6) was added, along with compound 3 additive which accounted for 1% of the total mass of the electrolyte, 1,3-propane sulfone (PS) which accounted for 2% of the total mass of the electrolyte, and fluoroethylene carbonate (FEC) which accounted for 5 wt% of the total mass of the electrolyte, and then uniformly stirred to obtain the electrolyte of a lithium-ion battery.
[0093] (2) Preparation of anode sheet: A lithium-ion battery anode slurry of constant viscosity was prepared by uniformly mixing lithium cobaltate material LiCoO2, conductive agent SuperP, adhesive PVDF, and carbon nanotubes (CNT) in a mass ratio of 96.8:2:1.2:0.05, and 330 g / m² 2 A lithium-ion battery positive sheet that meets the requirements was manufactured by applying a coating amount onto an aluminum foil for a current collector, drying and rolling to obtain a positive sheet.
[0094] (3) Preparation of cathode sheet: Artificial graphite and silicon are mixed in a mass ratio of 90:10, and then a slurry is prepared by mixing the conductive agent SuperP, the thickener CMC, and the adhesive SBR (butadiene styrene rubber latex) in a mass ratio of 95:1.5:1.5:2:2 and mixing them uniformly, and the mixed slurry is 157 g / m² 2 A lithium-ion battery negative sheet that meets the requirements was manufactured by applying a coating amount to both sides of a copper foil, drying and rolling to obtain a negative sheet.
[0095] (4) Manufacture of a lithium-ion battery: A lithium-ion battery with a thickness of 4.7 mm, a width of 55 mm, and a length of 60 mm was manufactured by laminating the positive electrode sheet, negative electrode sheet, and diaphragm manufactured according to the above-described process, and the battery was manufactured by vacuum baking at 85°C for 48 hours and injecting the above-described electrolyte.
[0096] Comparative Example 1
[0097] It is basically the same as Example 1, the only difference being that Compound 1 in the electrolyte is replaced with Comparative Compound 1.
[0098] Comparative Example 2
[0099] It is basically the same as Example 1, the only difference being that Compound 1 of the electrolyte is replaced with Comparative Compound 2.
[0100] Comparative Example 3
[0101] It is basically the same as Example 1, the only difference being that Compound 1 of the electrolyte is replaced with Comparative Compound 3.
[0102] Comparative Example 4
[0103] It is basically the same as Example 1, the only difference being that Compound 1 of the electrolyte has been removed.
[0104] Comparative Example 5
[0105] It is basically the same as Example 1, the only difference being that Compound 1 in the electrolyte is replaced with DTD.
[0106] Comparative Example 6
[0107] It is basically the same as Example 1, the only difference being that compound 1 in the electrolyte is replaced with LiPO2F2.
[0108] Comparative Example 7
[0109] It is basically the same as Example 4, the only difference being that Compound 1 in the electrolyte is replaced with Comparative Compound 1.
[0110] Comparative Example 8
[0111] It is basically the same as Example 4, the only difference being that Compound 1 of the electrolyte is replaced with Comparative Compound 2.
[0112] Comparative Example 9
[0113] It is basically the same as Example 4, the only difference being that Compound 1 of the electrolyte is replaced with Comparative Compound 3.
[0114] Comparative Example 10
[0115] It is basically the same as Example 4, the only difference being that compound 1 of the electrolyte has been removed.
[0116] Comparative Example 11
[0117] It is basically the same as Example 4, the only difference being that Compound 1 in the electrolyte is replaced with DTD.
[0118] Comparative Example 12
[0119] It is basically the same as Example 4, the only difference being that compound 1 in the electrolyte is replaced with LiPO2F2.
[0120] The electrolyte components and battery systems of Examples 1-6 and Comparative Examples 1-12 are as shown in Table 1 below.
[0121] Test items Electrolyte components battery system Example 1 EC:DEC:EMC:FEC:PS=20:25:32:5:2, 1% of compound 1 LiNi 0.8 Co 0.1 Mn 0.1 O2 / Silicon Carbon Example 2 EC:DEC:EMC:FEC:PS=20:25:32:5:2, 1% of compound 2 LiNi 0.8 Co 0.1 Mn 0.1 O2 / Silicon Carbon Example 3 EC:DEC:EMC:FEC:PS=20:25:32:5:2, 1% of compound 3 LiNi 0.8 Co 0.1 Mn 0.1 O2 / Silicon Carbon Comparative Example 1 EC:DEC:EMC:FEC:PS=20:25:32:5:2, 1% of comparative compound 1 LiNi 0.8 Co 0.1 Mn 0.1 O2 / Silicon Carbon Comparative Example 2 EC:DEC:EMC:FEC:PS=20:25:32:5:2, 1% of comparative compound 2 LiNi 0.8 Co 0.1 Mn 0.1 O2 / Silicon Carbon Comparative Example 3 EC:DEC:EMC:FEC:PS=20:25:32:5:2, 1% of comparative compound 3 LiNi 0.8 Co 0.1 Mn 0.1 O2 / Silicon Carbon Comparative Example 4 EC:DEC:EMC:FEC:PS=20:25:32:5:2 LiNi 0.8 Co 0.1 Mn 0.1 O2 / Silicon Carbon Comparative Example 5 EC:DEC:EMC:FEC:PS=20:25:32:5:2, 1% of DTD LiNi 0.8 Co 0.1 Mn 0.1 O2 / Silicon Carbon Comparative Example 6 EC:DEC:EMC:FEC:PS=20:25:32:5:2, 1% of LiPO2F2 LiNi 0.8 Co 0.1 Mn 0.1 O2 / Silicon Carbon Example 4 EC:DEC:EMC:FEC:PS=20:25:32:5:2, 1% of compound 1 LiCoO2 / Silicon Carbon Example 5 EC:DEC:EMC:FEC:PS=20:25:32:5:2, 1% of compound 2 LiCoO2 / Silicon Carbon Example 6 EC:DEC:EMC:FEC:PS=20:25:32:5:2, 1% of compound 3 LiCoO2 / Silicon Carbon Comparative Example 7 EC:DEC:EMC:FEC:PS=20:25:32:5:2, 1% of comparative compound 1 LiCoO2 / Silicon Carbon Comparative Example 8 EC:DEC:EMC:FEC:PS=20:25:32:5:2, 1% of comparative compound 2 LiCoO2 / Silicon Carbon Comparative Example 9 EC:DEC:EMC:FEC:PS=20:25:32:5:2, 1% of comparative compound 3 LiCoO2 / Silicon Carbon Comparative Example 10 EC:DEC:EMC:FEC:PS=20:25:32:5:2 LiCoO2 / Silicon Carbon Comparative Example 11 EC:DEC:EMC:FEC:PS=20:25:32:5:2, 1% of DTD LiCoO2 / Silicon Carbon Comparative Example 12 EC:DEC:EMC:FEC:PS=20:25:32:5:2, 1% of LiPO2F2 LiCoO2 / Silicon Carbon
[0122] Performance test
[0123] (1) High-temperature cycle performance test:
[0124] A battery formed at 45℃ was charged to 4.2V with a constant current of 0.02C and a constant voltage, and discharged to 2.75V with a cutoff current of 0.01C and a constant current of 1C. After performing N cycles of charging and discharging in this manner, the high-temperature cycle performance was evaluated by calculating the capacity retention rate after the Nth cycle.
[0125] The formula for calculating the capacity retention rate for N cycles at 45℃ and 1C is as follows.
[0126] Nth cycle capacity retention rate (%) = (Nth cycle discharge capacity / 1st cycle discharge capacity) × 100%.
[0127] (2) 60℃ High Temperature Storage Performance Test:
[0128] The formed battery was charged to 4.2V at room temperature with a constant current and voltage of 1C and a cutoff current of 0.01C, and then discharged to 2.75V with a constant current of 1C to measure the initial discharge capacity of the battery. After charging again to 4.2V with a constant current and voltage of 1C and a cutoff current of 0.01C and measuring the initial thickness of the battery, the battery was stored at 60℃ for N days, and then the thickness of the battery was measured. After discharging again to 2.75V with a constant current of 1C and measuring the battery's retention capacity, the battery was charged again to 4.2V with a constant current of 1C and a constant voltage of 0.01C and discharged to 2.75V with a constant current of 1C to measure the recovery capacity. The calculation formulas for the capacity retention rate and capacity recovery rate are as follows.
[0129] Battery capacity retention rate (%) = Retained capacity / Initial capacity × 100%;
[0130] Battery capacity recovery rate (%) = Recovered capacity / Initial capacity × 100%;
[0131] Battery thickness expansion rate (%) = (Thickness after N days - Initial thickness) / Initial thickness × 100%
[0132] After performing DC impedance (DCR) and internal resistance tests at room temperature on the oxidized battery, the battery was stored at 60°C for N days, and then DCR and internal resistance tests were performed again at room temperature. The calculation formulas for the rate of change of DCR and internal resistance before and after high-temperature storage are as follows.
[0133] Rate of change in battery internal resistance (%) = (Internal resistance after N days - Internal resistance before storage) / Internal resistance before storage × 100%
[0134] (3) 20℃ Low-temperature discharge performance test:
[0135] At room temperature (25℃), a 1C / 1C charge and discharge cycle was performed once on the lithium-ion battery, with an upper limit voltage of 4.2V and the discharge capacity C0 was recorded. After leaving the battery in a -20℃ environment for 4 hours, it was discharged to 2.75V with a 1C current and the discharge capacity C1 was recorded, and the lithium-ion battery -20℃ discharge rate was calculated using the following formula.
[0136] -20℃ Discharge Rate = C1 / C0 * 100%
[0137] After manufacturing a lithium-ion battery using the electrolyte of the above-described example, the room temperature cycle performance, high temperature cycle performance, and low temperature discharge performance of the lithium-ion battery were tested, and the results are shown in Table 2.
[0138] Lithium-ion battery performance test results Test items After storing at 60℃ for 7 days 45℃ 1C 500 week cycles -20℃ 1C discharge rate Maintenance capacity Recovery capacity Thickness expansion DCR change rate Capacity retention rate Example 1 92% 96% 5% -5% 88% 70% Example 2 86% 89% 10% 8% 83% 67% Example 3 85% 88% 12% 10% 82% 66% Comparative Example 1 75% 78% 19% 20% 75% 60% Comparative Example 2 73% 75% 22% 25% 74% 59% Comparative Example 3 76% 80% 19% 35% 68% 61% Comparative Example 4 65% 67% 30% 55% 60% 65% Comparative Example 5 77% 82% 18% 30% 75% 65% Comparative Example 6 73% 78% 24% 33% 70% 68% Example 4 90% 95% 5% -3% 87% 72% Example 5 85% 88% 12% 12% 83% 65% Example 6 84% 88% 14% 11% 82% 66% Comparative Example 7 76% 79% 21% 22% 76% 57% Comparative Example 8 73% 76% 25% 26% 75% 54% Comparative Example 9 71% 75% 18% 30% 72% 52% Comparative Example 10 62% 66% 32% 56% 62% 57% Comparative Example 11 75% 80% 15% 32% 73% 54% Comparative Example 12 72% 75% 20% 35% 71% 59%
[0139] As can be clearly seen from Table 1, the technical effects of Examples 1 to 6 are significantly superior to those of Comparative Examples 1 to 12, and in particular, Examples 1 and 4 are significantly superior; that is, when Compound 1 is used as an electrolyte additive, it has a significant advantage in terms of reducing battery impedance change and battery expansion rate after high-temperature storage. It explains that the electrolyte additive has a significant effect on the capacity retention rate and high-temperature cycle of the lithium-ion battery, and that by adopting the electrolyte additive of the present invention, the capacity retention rate at room temperature and high-temperature cycles and the high-temperature cycle capacity retention rate of the battery are effectively improved. A battery containing the electrolyte of the present invention has better high-temperature cycle performance, reduces battery thickness expansion during high-temperature storage periods, and reduces impedance change.
[0140] Each technical feature of the aforementioned embodiments may be combined arbitrarily, and for the sake of brevity, not all possible combinations of each technical feature among the embodiments described above have been described; however, as long as there is no contradiction in such combinations of technical features, they should all be deemed to be within the scope described herein.
[0141] The foregoing embodiments merely represent a few embodiments of the present invention, and while the description is relatively specific and detailed, it should not be understood as limiting the scope of the patent of the present invention. Those skilled in the art should note that various modifications and improvements can be made without departing from the concept of the present invention, and that all of these fall within the scope of protection of the present invention. Accordingly, the scope of protection of the patent of the present invention shall be based on the appended claims.
Claims
Claim 1 In a substituted silicon group phosphate compound, used as an electrolyte additive, having the structure shown in Formula (I), (I) Here, R1, R2, R3, R4, R5, R6, R7, R8, and R9 are each independently C 1-8 Alkyl, C 2-8 Alkenyl or C 2-8 Selected from alkynyl; also, at least one of R1, R2, and R3 is C 1-8 They are alkyl, and one of them is C 2-8 Alkenyl or C 2-8 It is an alkynyl; at least one of R4, R5, and R6 is C 1-8 They are alkyl, and one of them is C 2-8 Alkenyl or C 2-8 It is alkynyl; at least one of R7, R8, and R9 is C 1-8 They are alkyl, and one of them is C 2-8 Alkenyl or C 2-8 A substituted silicon phosphate compound characterized by being alkynyl. Claim 2 A substituted silicon group phosphate compound according to claim 1, characterized in that R1, R3, R4, R6, R7, and R9 are each independently selected from methyl, ethyl, 1-propyl, 2-propyl, 1-butyl, 2-methyl-1-propyl, or 2-butyl; and R2, R5, and R8 are each independently selected from vinyl, ethynyl, allyl, or propargyl. Claim 3 A substituted silicon group phosphate compound according to claim 1, characterized in that R1, R3, R4, R6, R7, and R9 are each independently selected from vinyl, ethinyl, allyl, or propargyl; and R2, R5, and R8 are each independently selected from methyl, ethyl, 1-propyl, 2-propyl, 1-butyl, 2-methyl-1-propyl, or 2-butyl. Claim 4 A substituted silicon group phosphate compound according to claim 1, characterized in that -SiR1R2R3, -SiR4R5R6 and -SiR7R8R9 are identical to each other. Claim 5 A substituted silicon group phosphate compound according to claim 1, characterized by being selected from any of the following compounds. Claim 6 The additive comprises an additive, wherein the additive comprises a first additive, and the first additive is a substituted silicon group phosphate compound having the structure shown in formula (I). (I) Here, R1, R2, R3, R4, R5, R6, R7, R8, and R9 are each independently C 1-6 Alkyl, C 2-6 Alkenyl or C 2-6 Selected from alkynyl; also, at least one of R1, R2, and R3 is C 1-6 They are alkyl, and one of them is C 2-8 Alkenyl or C 2-8 It is an alkynyl; at least one of R4, R5, and R6 is C 1-6 They are alkyl, and one of them is C 2-8 Alkenyl or C 2-8 It is alkynyl; at least one of R7, R8, and R9 is C 1-6 They are alkyl, and one of them is C 2-8 Alkenyl or C 2-8 Electrolyte characterized by being alkynyl. Claim 7 An electrolyte according to claim 6, wherein the additive further comprises a second additive, and the second additive is one or more of vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, vinyl sulfite, vinyl sulfate, 1,3-propane sulfonic acid lactone, dispiropropylene sulfate, tetraethylenesilane, hexamethylene diisocyanate, and lithium difluorophosphate. Claim 8 An electrolyte according to claim 6, characterized in that the mass percentage content of the additive in the electrolyte is 0.05% to 20.0%. Claim 9 An electrolyte according to claim 6, further comprising a lithium salt and a solvent, wherein the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium dioxalate borate, lithium difluorooxalate borate, lithium bisfluorosulfonyl imide, and lithium bistrifluoromethanesulfonyl imide; and wherein the solvent is selected from one or more of chain-type carbonates, cyclic carbonates, and carboxylates. Claim 10 An electrolyte according to claim 7, characterized in that, in the electrolyte, the mass percentage content of the first additive is 0.1%-15% and the mass percentage content of the second additive is 0.1%-5%. Claim 11 A lithium-ion battery characterized by comprising a positive electrode, a negative electrode, and an electrolyte described in any one of claims 6 to 10.
Citation Information
Patent Citations
Lithium secondary battery
KR1020150048658A
Electrolyte for non-aqueous electrolyte battery and non-aqueous electrolyte battery using the same
KR1020190079695A
